A recombinant matrix metalloproteinase protein from gnathostoma spinigerum for serodiagnosis of neurognathostomiasis - Penchom Janwan (2018)
Neurognathostomiasis is a severe form of human gnathostomiasis which can lead to disease and death. Diagnosis of neurognathostomiasis is made presumptively by using clinical manifestations. Immunoblotting, which recognizes antigenic components of molecular mass 21 kDa and 24 kDa in larval extracts of Gnathostoma spinigerum (Gs 21/24), has high sensitivity and specificity for diagnosis of neurognathostomiasis. However, only very small amounts of the Gs 21/24 antigens can be prepared from parasites harvested from natural or experimental animals. To overcome this problem, we recently produced a recombinant matrix metalloproteinase (rMMP) protein from G. spinigerum. In this study, we evaluated this rMMP alongside the Gs 21/24 antigens for serodiagnosis of human neurognathostomiasis. We studied sera from 40 patients from Srinagarind Hospital, Khon Kaen University, Thailand, with clinical criteria consistent with those of neurognathostomiasis, and sera from 30 healthy control adults from Thailand. All sera were tested for specific IgG antibodies against both G. spinigerum crude larval extract and rMMP protein using immunoblot analysis. The sensitivity and specificity for both antigenic preparations were all 100%. These results show that G. spinigerum rMMP protein can be used as an alternative diagnostic antigen, in place of larval extract, for serodiagnosis of neurognathostomiasis. © 2013, Korean Society for Parasitology and Tropical Medicine.